The Efficacy Of Radiocolloid In Sentinel Lymph Node Biopsy In Early-stage Breast Cancer - Bolhan, Hayatul Azuwa (2021)
Purpose: This study aims to evaluate the performance of radiocolloid, blue dye and combined method in sentinel lymph node biopsy in early breast carcinoma. Methods: One hundred seventy-two clinically node-negative, early-staged breast cancer patients who underwent SLNB with combined radiocolloid and blue dye were recruited. The numbers of hot node and blue node were analysed in all patients, all excised nodes and metastatic nodes patients, giving rise to the detection rate, metastatic rate and failure rate of combined method, radiocolloid and blue dye method. The association between the clinicopathological factors and the SLN detection was also analysed. Results: Out of 172 patients, the presence of a hot node and a blue node were 98.2% (169/172) and 95.9% (165/172) respectively. The overall SLN detection rate through combined method was 99.4% (171/172) and metastatic rate was 19.2% (33/172). Among the 33 metastatic-node patients, the combined method, radiocolloid and blue dye method failed to identify 1, 1 and 4 patients respectively. Therefore, the failure rate of the combined method, radiocolloid and blue dye method were 3.0% (1/33), 3.0% (1/33) and 12.1% (4/33), respectively. No significant finding was observed to associate clinicopathological factors and the SLN detection. Conclusion: This study showed the combined method of SLNB yielded the highest detection rate when compared to radiocolloid-alone and blue dye-alone method. More SLN was detected by radiocolloid method than blue dye method. Therefore, incorporating radiocolloid method in the blue dye method will improve SLN identification rate and reduce the failure rate of metastatic detection.